2009
DOI: 10.1021/jf802610p
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Some Carotenoids and Apocarotenoids during Flower Development in Boronia megastigma (Nees)

Abstract: The carotenoid profile of an acetone extract from the flowers and leaves of Boronia megastigma (Nees) was examined. A comparison was made of the major carotenoids found in boronia flowers and leaves. The C-40 carotenoids beta-carotene, zeaxanthin, lutein, and neoxanthin were positively identified in boronia flowers using known standards, UV-vis spectra, and mass spectrometry. Two other carotenoids were tentatively assigned as the palmitic acid ester of 3-hydroxy-10'-apocaroten-10'-oic acid and 9,15,9'-tri-cis-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…For instance, the petals of Eschscholzia californica (Papaveraceae) accumulate crocetin among other carotenoids [48] and those of Crocosmia (Iridaceae) accumulate crocin [49]. Various apocarotenoids such as β-ionone, 10′-apocaroten-10′-oic acid, and hydroxy 10′-apocaroten- 10′-oic acid are found in the petals of Boronia megastigma [50].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the petals of Eschscholzia californica (Papaveraceae) accumulate crocetin among other carotenoids [48] and those of Crocosmia (Iridaceae) accumulate crocin [49]. Various apocarotenoids such as β-ionone, 10′-apocaroten-10′-oic acid, and hydroxy 10′-apocaroten- 10′-oic acid are found in the petals of Boronia megastigma [50].…”
Section: Discussionmentioning
confidence: 99%
“…In plants, they play key roles in reproduction, defense, and architecture [50]. 3-OH-β-Apo-10’-carotenoic acid has been identified in Boronia megastigma (Nees) during flower development, indicating cleavage of xanthophylls and oxidation of cleavage products [51, 52]. In animals, a number of studies have identified a broad array of apocarotenoids and apolycopenoids with potential biological activities [7, 18, 20, 53, 54].…”
Section: Discussionmentioning
confidence: 99%
“…The Xowers of this small shrub native to southwestern Australia are collected for their Xavor and fragrance based on various C 13 apocarotenoid constituents (Cooper et al 2003). A palmitic ester of a C 27 3-hydroxy-10Ј-apocaroten-10Јoic acid and other C 27 apocarotenoids have been tentatively identiWed recently from this system (Cooper et al 2009). Based on C 27 identiWcation in rose petals, such a two-step sequential cleavage mechanism has been proposed for C 13 scent and aroma compound biogenesis many years ago (Eugster and Märki-Fischer 1991), but this mechanistic proposal has never been substantiated by enzymatic data and fell into oblivion in the wake of many studies showing dual 9-10 and 9Ј-10Ј cleavage activity of recombinant CCD1 proteins on various C 40 carotenoids in vitro.…”
Section: Role Of Ccd1 In Mycorrhizal Roots and Beyondmentioning
confidence: 99%